ATRIAL FIBRILLATION OR FLUTTER IN THE EARLY POSTOPERATIVE PERIOD AFTER ASCENDING AORTA AND/OR AORTIC VALVE REPLACEMENT: RISK FACTORS, TREATMENT, PREVENTIVE MAINTENANCE - V. V. Ionova; M. L. Semenovsky (Вестник трансплантологии и искусственных органов, 2010)
Atrial fibrillation or flutter (AF) are frequent complication after replacement of cardiac valves including prosthe- tics of ascending aorta and/or aortic valve, and can cause the infringement of haemodynamics, development of thromboembolic complications, and also increase duration of hospitalisation and treatment cost. The work pur- pose was the attempt to define the most frequent reasons of development AF in early terms after ascending aorta and/or aortic valve replacement, and also medical and preventive tactics at occurrence of these complications.